Anti-SRP immune-mediated necrotizing myopathy: A critical review of current concepts - Ma, Xue; Bu, Bi-Tao (Frontiers in Immunology, 2022)
Purpose of review This review aims to describe clinical and histological features, treatment, and prognosis in patients with anti-signal recognition particle (SRP) autoantibodies positive immune-mediated necrotizing myopathy (SRP-IMNM) based on previous findings. Previous findings Anti-SRP autoantibodies are specific in IMNM. Humoral autoimmune and inflammatory response are the main autoimmune character of SRP-IMNM. SRP-IMNM is clinically characterized by acute or subacute, moderate severe, symmetrical proximal weakness. The younger patients with SRP-IMNM tend to have more severe clinical symptoms. Patients with SRP-IMNM may be vulnerable to cardiac involvement, which is ought to be regularly monitored and recommended to be detected by cardiac magnetic resonance imaging. The pathological features of SRP-IMNM are patchy or diffuse myonecrosis and myoregeneration accompanied by a paucity of inflammatory infiltrates. Endoplasmic reticulum stress-induced autophagy pathway and necroptosis are activated in skeletal muscle of SRP-IMNM. Treatment of refractory SRP-IMNM encounters resistance and warrants further investigated. Summary Anti-SRP autoantibodies define a unique population of IMNM patients. The immune and non-immune pathophysiological mechanisms are involved in SRP-IMNM.